Analisis Pembangunan Inklusif dan Industrialisasi terhadap Kesejahteraan dalam Perspektif Ekonomi Islam - Anjani, Dita Nabila; Ekawati, Evi; Satriawan, Dedi (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
Indonesia's economic growth has shown a positive trend in the last decade. Income inequality and unequal access to resources are still major issues for people's welfare. Inclusive development and industrialization have emerged as alternative solutions to address these challenges. This study aims to analyze the impact of inclusive development and industrialization on welfare in Indonesia. This type of research is quantitative with an explanatory design, using secondary data from the Central Statistics Agency (BPS) and other official institutions from 2012–2022. The analysis method used is panel data regression. Inclusive development indicators are measured through the inequality index (Gini Ratio), labor force participation rate, and local government social spending. Industrialization is measured by the industrial sector's contribution to GDP, the number of industrial business units, and labor absorption. People's welfare is represented by the Human Development Index (HDI), poverty rate, and open unemployment. The study results show that inclusive development contributes significantly to increasing welfare, mainly through reducing inequality and increasing HDI. Industrialization has a positive impact, but its influence is more maximal if accompanied by a fair economic distribution policy. This study emphasizes the importance of integrating industrialization strategies and inclusive approaches to achieve sustainable and equitable prosperity.